Konsociační demokracie a její alternativy v plurálních společnostech: příspěvek k 50. výročí jedné teorie - Jakub Charvát (Acta Politologica, 2018)
The aim of this text is to commemorate the fiftieth anniversary of the theory of consociational democracy. Following an introduction, discussion and criticism of this theory, the paper briefly discusses other selected models of institutional arrangements being designed to facilitate stable democracies in divided societies, centripetalism or integrative (inclusive) majoritarianism and integrative consensualism, respectively. These two models of conflict management in plural societies have grown from the criticism of the original consociational framework. While the consociational model is based on a communal perspective and its main objectives are inclusiveness and proportionality, the latter two models build on an integrative perspective on conflict management in plural societies while they place the main emphasis on electoral system as a key institution for inter-ethnic accommodation. While centripetalism focuses on the moderation and accommodation of conflict, integrative consensualism seeks to synthesize both previous models to eliminate their shortcomings and to show their positive qualities. Empirical experience, however, shows that all the theoretical models represent “only” ideal types of conflict management. In the practice of constitutional engineering in heterogenous societies, there are often different combinations of these approaches, and rarely one of these types is applied in terms of the divided companies in pure form.